Power System Node Loadability Evaluation Using Flexibility Analysis Method - Sun, W. Q.; Xia, K.; Li, H. Y.; Wang, C. M. (Elektronika ir Elektrotechnika, 2014)
System transfer capability evaluation is an important research topic in power system analysis. However, as the uncertainty of load increasing direction, researches on the upper bound of system transfer capability appear to be too optimistic, whereas researches on the lower bound of system transfer capability appear to be too pessimistic. Actually, as load increasing direction cannot be forecasted accurately in practical power systems, obvious flaws in evaluating system transfer capability using deterministic analysis methods exist. In this paper, a method is proposed to give an approximate evaluation on power system node loadability using flexibility analysis method. Conventional rigid node voltage constraints are expressed into flexible form, and a set of critical node voltage values are obtained by solving a standard nonlinear optimization model using interior point algorithm. With the adjustment strategies given, such critical node voltage values show a strong positive correlation with the loadability on the corresponding nodes. Besides, compared with conventional methods, the method proposed can significantly improve the calculation efficiency for the same research purpose. Case study on IEEE 30-bus test system validates the effectiveness of the method proposed. DOI: http://dx.doi.org/10.5755/j01.eee.20.6.7267